Dementia associated mental and behavioural disturbances in elderly people in the community: findings from the first Nakayama study. Issue 1 (5th January 2004) - Ikeda, M; Fukuhara, R; Shigenobu, K; Hokoishi, K; Maki, N; Nebu, A; Komori, K; Tanabe, H
Abstract : Objective: To determine the prevalence of mental and behavioural disturbances associated with dementia in elderly people living in the Japanese community of Nakayama. Methods: A door to door three phase population survey was carried out on all persons aged 65 years and older living at home. The study included a psychiatric interview, neurological and neuropsychological examination, and cranial computed tomography. Participants with dementia were rated on the neuropsychiatric inventory. Results: Of 1438 inhabitants, 1162 (81.0%) completed the protocol. The prevalence of dementia was 4.8%. Of the 60 participants with dementia (Alzheimer's disease 35%, vascular dementia 47%, and dementia from other causes 17%), 53 (88.3%) had shown one or more mental and behavioural disturbances. Apathy/indifference (56.7%), followed by agitation/aggression (35%), aberrant motor behaviour (31.7%), and irritability (31.7%) were the common symptoms. More productive (positive) symptoms such as delusions and aberrant motor behaviour were found in the Alzheimer group than in the vascular dementia group. Conclusions: A wide range of dementia associated mental and behavioural disturbances developed in the majority of community dwelling individuals with dementia. The findings suggest that a screening programme focusing on identifying these symptoms should be included in the physician's diagnostic tools for dementia.